Negative Implications of Maternal and Neonatal Outcomes in Pregnancy Associated with Anemia, Aljouf, Saudi Arabia (African Journal of Biomedical Research, 2024)
One of the most prevalent serious health issues is anemia. It is a high-risk condition since it has negative pregnancy-related effects on both the mother and the fetus. The most vulnerable population to anemia is pregnant women. This research was done in Aljouf, Saudi Arabia, to find out the negative effects of anemia on maternal and fetal outcomes during pregnancy. Retrospective research was conducted on pregnant patients treated at the Maternity and Children Hospital (MCH), Sakaka, Aljouf, Saudi Arabia, over a 12-month period. All 480 pregnant women provided the necessary information, which included demographics like age, education, socioeconomic status, parity, birth intervals, trimester of pregnancy, BMI, history of fever, neonatal information, and investigative data. Participants with anemia during pregnancy totaled 485; mild anemia made up 18.7%, moderate anemia 77.9%, and severe anemia 3.2%. The age group of 30-34 years saw the highest prevalence of anemia (32.5%), multiparity (51.7%), and secondary education (51.7%). While 73.6% anemia found in first trimester,63% in overweight women and 73.6% less than 2 years of birth intervals. Out of 485, 145 had abortions, and the remaining 340 expectant mothers had fetal distress at a rate of 14.4%, IUGR at a rate of 6.7%, LBWB at a rate of 10.8%, a cardiac anomaly at a rate of 0.2%, and 6.7% were admitted to the NICU. All anemic pregnant women have their blood hematocrit levels examined as well. For associated risk factors including fever, parity, and social classes, use multivariate analysis. Our study's pregnant participants were severely anemic, which had negative impacts on the developing fetus and newborn. The linked factors that contributed to the development of anemia during pregnancy must be improved.
Keywords: Anemia; pregnancy; pregnancy outcomes